Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1161/circheartfailure.111.962787
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Functional Correlates of Early Microvascular Dysfunction After Heart Transplantation

Abstract: A history of acute rejection during the first year and smaller donor hearts were identified as risk factors for early microvascular dysfunction. Microvascular dysfunction assessed using index of microcirculatory resistances at 1 year was also associated with worse graft function and possibly worse clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 34 publications
1
44
1
Order By: Relevance
“…In addition, the IMR measurement at 1 year was an independent predictor of death or retransplantation, while IVUS parameters were not, suggesting that microvascular function may be a more important indicator of long-term outcome as compared to epicardial plaque. Moreover, in another study IMR was found to predict development of CAV and graft dysfunction (13). In non-transplant recipients IMR has also been found to be useful in identifying the cause of chest pain in patients with non-obstructive epicardial coronary disease and in predicting poor recovery of left ventricular function and mortality when measured after primary percutaneous coronary intervention in patients with ST segment elevation myocardial infarction (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the IMR measurement at 1 year was an independent predictor of death or retransplantation, while IVUS parameters were not, suggesting that microvascular function may be a more important indicator of long-term outcome as compared to epicardial plaque. Moreover, in another study IMR was found to predict development of CAV and graft dysfunction (13). In non-transplant recipients IMR has also been found to be useful in identifying the cause of chest pain in patients with non-obstructive epicardial coronary disease and in predicting poor recovery of left ventricular function and mortality when measured after primary percutaneous coronary intervention in patients with ST segment elevation myocardial infarction (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Cutoff values of 20 for baseline and 1-year IMR, 2.5 for baseline and 1-year CFR, 0.90 for baseline FFR, and 0.85 for 1-year FFR were obtained from the literature. 10,14 Time-to-event data were analyzed with the Kaplan-Meier method and compared by use of the log-rank test. Cox regression analysis was performed to determine predictors of death/retransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be explained by the facts that microvascular dysfunction at 1 year is associated with impaired ventricular function and that an increase in IMR correlates with a decrease in cardiac index and stroke volume index and more hemodynamically compromising rejection. 10 The lack of correlation between an elevated IMR at baseline and outcomes implies that whatever factors contribute to an abnormal IMR at baseline (eg, inflammation and edema resulting from the transplantation process) are likely not important mediators of long-term outcome. Others have reported that in the absence of significant epicardial CAV, episodes of rejection are associated with microvascular dysfunction, 24 which also was found in this study.…”
Section: Importance Of Microvascular Dysfunctionmentioning
confidence: 99%
“…While a variety of post-transplant complications may explain this later attrition, common predictors of late survival including perioperative renal function and rejection episodes are similar between the two groups. Possible reasons include a higher incidence of microvascular dysfunction associated with undersized donor hearts,[16] which may be more likely with greater gender mismatch seen in the IABP group. It is important to re-emphasize; however, that upon risk-adjusted analysis the post-transplant survival between groups was equivalent.…”
Section: Discussionmentioning
confidence: 99%